The Impact of Hiring Individuals with Intellectual Disability on Employer: Experience, Perception, Motivation and Social Responsibility - Idris, Nadzimah; Razalli, Abdul Rahim; Mohd Jamil, Mohd Ridhuan; Hosshan, Hasrul (Jurnal Pendidikan Bitara UPSI, 2023)
Intellectual disability is a condition that impairs cognitive functioning, and it can deviate from typical characteristics. People with intellectual disabilities often face limited employment prospects because of unfavorable employer perceptions. This case study delves into the effects of employing an individual with intellectual disabilities on the employer. It focuses on their experiences, perceptions, motivations, and sense of social responsibility. The research methodology employed in the study encompassed interviews and observations, with a sample size of three participants. The findings demonstrate that five key themes influence the recruitment and retention of individuals with intellectual disabilities in the labor force: understanding intellectual disabilities, the recruitment process, current work arrangements, employment prospects, and compensation packages. This research study provides valuable insights for scholars to comprehend employers’ perceptions and interactions with individuals with intellectual disabilities within the industrial sector. Additionally, it aids in identifying competitive human resources with intellectual disabilities that can effectively fulfill industry requirements in the coming years.